Trend Analysis of Bed Occupancy Rate (BOR) in National Referral Hospitals Post-COVID-19 Pandemic: Implications for Administrative Resource Allocation Policies - Utami; Riska Nuryana (CV. Get Press Indonesia, 2025)
The Bed Occupancy Rate (BOR), a critical efficiency metric, experienced unprecedented volatility during the COVID-19 pandemic, necessitating a re-evaluation of its long-term trajectory in the National Referral Hospital (NRH) network.1 This study's purpose was to model the aggregate BOR trend in NRHs post-pandemic and empirically identify its principal administrative determinants. Methods involved a quantitative time-series design, utilizing aggregated monthly operational data from all Indonesian Type A and B NRHs (Kemenkes RI/SIRS) from January 2019 to December 2023. Analysis used a Segmented Regression Model (SRM), incorporating regional dummy variables for contextual robustness, and multivariate regression. Statistical robustness was confirmed by model fit and turning point significance (p < 0.05). Results demonstrate a significant structural shift: the mean BOR stabilized at 69.4% (p < 0.01), confirming sustained underutilization below the optimal 75% benchmark. The SRM indicated a permanent 3.5 percentage point decline post-crisis. Key determinants were found to be negatively correlated with telemedicine adoption (2), which diverts low-acuity demand, and positively correlated with the launch of high-acuity specialty services (3), confirming complex demand concentration.4 Implications are that the traditional BOR metric is now obsolete, mandating an immediate revision of administrative resource allocation policies. The conclusion is that NRHs must undergo a paradigm shift to embrace specialization, requiring investment in high-acuity services and the adoption of a Complexity-Adjusted Utilization Index (CABOR) to achieve a sustainable, complex-care-focused operational equilibrium.5 Follow-up qualitative studies (interviews) are recommended to validate the operational significance of the low BOR.